MORPHOLOGICAL AND FUNCTIONAL MODIFICATIONS DURING THE PROCESS OF AGEING. CHARACTERISTICS AND BENEFITS OF PHYSICAL ACTIVITY - Paola Vago; Nicola Lovecchio (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2014)
Ageing is a slow but dynamic process, which involves many internal and external influences. It is a complex multifactorial phenomenon characterized by progressive physiological, genetic, endocrinological and molecular changes, responsible for the increased risk of morbidity and death. Because of an increase in life expectancy, the incidence of degenerative diseases, such as muscular and skeletal diseases will also increase. The age-associated loss of skeletal muscle mass and strength (i.e. sarcopenia) seems to be an unavoidable part of the physical human decline. In fact, the relationship of ageing with impaired physical performance, frailty, loss of functional independence and increased risks of falls are well established in the literature. In addition, decreased muscle strength is also highly predictive of incident disability in the elderly. In particular, weakness and functional deficit have been considered hallmark predictors of age related morbidity and decreased autonomy. Research on ageing has traditionally been concerned with health, but recently the concept of functional capacity has also been attracting growing attention. Regular physical activity, including, muscle-strengthening activity such as resistance exercises, balance and flexibility exercises, aerobic activity, is essential to develop a strategy to delay ageing.